The Effect between Product Quality and Promotional Activities on Consumer Purchase Interest (A Case Study of Garuda Peanut Products Produced by PT. Garudafood, Tbk) - Udin Ahidin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims to determine the effect of product quality and promotional activities on consumer buying interest (Case Study of Garuda Peanut Products Produced by PT. Garudafood, Tbk). The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study, product quality has a significant effect on purchase intention by 45.2%, hypothesis testing obtained t count > t table or (8.990> 1.984). Promotional activities have a significant effect on purchase intention by 37.1%, hypothesis testing is obtained t count> t table or (7.599> 1.984). Product quality and promotional activities simultaneously have a significant effect on buying interest with the regression equation Y = 10.422 + 0.434X1 + 0.312X2 and the contribution of the effect is 52.2%, the hypothesis test obtained F count> F table or (53.010> 2,700).